Analisis Dan Estimasi Kinerja Bank Umum Syariah Sebelum Dan Selama Pandemi Covid-19 - Adin Jaelani Sopian; Rifki Ismal; Yono Haryono (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2023)
This study aims to determine and analyze the influence of macroeconomic and internal financial performance factors of Islamic Commercial Banks on the profitability of Islamic Commercial Banks before and during the COVID-19 pandemic, as well as to be able to estimate the long-term and short-term effects on the financial performance of Islamic Commercial Banks. The data analysis method in this study uses the Error Correction Model (ECM), where the end result is to measure the short-term and long-term influence of the movement of Islamic Commercial Bank profitability as measured by ROA. The data used is secondary data, in the form of time series and the research period is January 2015 - December 2022. The results showed that interest rates (SB), exchange rates (NTR), NPF, CAR and BOPO affect ROA in the long run. While NPF, BOPO and SB have an effect on ROA in the short term. These findings are very important for the Islamic banking industry and the authorities to carry out strategies that must be carried out on the influence of macroeconomics and internal financial performance of Islamic Commercial Banks